Evaluation of KUB Chicken Carcass Dimensions Based on Slaughter Age and Sex - Indarsih, Budi; Rozi, Tapaul; Jaya, I Nyoman Sukartha; Haryani, Ni Ketut Dewi; Tamzil, Moh Hasil; Septian, I Gede Nano; Umrah, Umrah (Faculty of Animal Husbandry, University of Mataram, 2025)
This study investigated the influence of slaughter age and sex on carcass dimensions in KUB chickens. A Randomized Block Design with a 2 x 4 factorial layout was used, incorporating two variables: sex (male and female) and slaughter age (4, 6, 8, and 10 weeks). Each treatment group included 10 chickens, evenly divided between males and females. The parameters measured included the length and width of the upper and lower thigh, wing length, and the length and width of the breast and back. The results showed that slaughter age had a significant effect (P<0.05) on all measured traits, including thigh and wing sizes, breast dimensions, and the back length and width. Sex also had a significant influence on upper thigh dimensions, breast length, and back size. Additionally, there was a significant interaction between sex and slaughter age for upper thigh size, wing length, and breast dimensions (P<0.05). The most substantial carcass measurements were observed in chickens slaughtered at 10 weeks of age. Male KUB chickens had carcass dimension was higher than the females.